Illusory shrinkage of objects under backward masking - Sae Kaneko; Stuart Anstis; Patrick Cavanagh (i-Perception)
Backward masking is a powerful phenomenon that can reduce, often to zero, the visibility of targets. Here, we show that when the masking is less than completely effective so that the target remains visible, the masking has other effects, specifically reducing the perceived size of the target.